Analisis Kondisi Sosial Ekonomi Masyarakat Suku Tengger di Desa Ngadisari Kecamatan Sukapura Kabupaten Probolinggo - Babul Bahrudin (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2022)
This study is aimed to analyze the socio-economic conditions of the Tengger Tribe community in Ngadisari Village, Sukapura District, Probolinggo Regency., as well as the impact of Mount Bromo tourism on the economy of the Tengger Tribe community in Ngadisari Village. In this study, the researchers use a qualitative approach. Data collection techniques were carried out through in-depth interviews, observation and documentation. The validity of the data used source triangulation techniques and theoretical triangulation. In the Data analysis techniques, the researchers use data collection, data reduction, data presentation, and data verification or conclusions. This researchers examine the socio - economic conditions of the Tengger tribe. The focus of the study in this research includes the livelihoods of the Tenggerese people, as well as the impact of tourism in Bromo Tengger Semeru National Park on the changes in space or economic activity of the Tenggerese people. Research results show that people in the Mount Bromo area make a living as vegetable farmers, tourism service providers and as trader. With the existence of Mount Bromo as a tourist spot that is much favored by tourists, the economy of the Tengger people in the Mount Bromo area is getting better.